First-Principles Atomistic Thermodynamics and Configurational Entropy - Sutton, Christopher; Levchenko, Sergey V. (Frontiers in Chemistry, 2020)
In most applications, functional materials operate at finite temperatures and are in contact with a reservoir of atoms or molecules (gas, liquid, or solid). Thus, in order to understand materials properties at realistic conditions, statistical effects associated with configurational sampling and particle exchange at finite temperatures must be taken into account. In this contribution, we discuss the main concepts of equilibrium statistical mechanics. We demonstrate how these concepts can be used to predict behavior of materials at realistic temperatures and pressures within the framework of atomistic thermodynamics. Methods for calculating phase diagrams of bulk materials and surfaces, as well as, point defect concentrations are introduced and discussed. In particular, we describe approaches for calculating configurational density of states, which requires the accurate evaluation of the relative energies for a large number of configurations. Therefore, we also discuss the cluster expansion method, which is a numerically efficient method for evaluating larger configuration spaces while only knowing the energies of a small subset of all possible configurations.